Major Accident Hazard Analysis and Determination of Safety Critical Elements at Gresik Gas Distribution Station Using the HAZOP Method - Jasillatul Hikmiyah; Dyah Santhi Dewi; Nurhadi Siswanto (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2026)
The Gresik Gas Distribution Station (GDS) is a critical natural gas facility operating under high-pressure conditions, where process failures may lead to Major Accident Hazards (MAHs). Therefore, systematic hazard identification is essential to ensure process safety and operational reliability. This study aims to identify potential MAHs and determine the Safety Critical Elements (SCEs) required to prevent and manage these hazards. The study employed the Hazard and Operability Study (HAZOP) method to evaluate three key process nodes: the metering and regulating system, odorant injection system, and instrument air system. Process deviations were analyzed using guide words, followed by risk assessment to identify MAHs. Safety Critical Elements were subsequently identified based on their safety functions, including the prevention, detection, control, mitigation, and recovery of MAH events. The analysis identified 17 potential causes classified as Major Accident Hazards and 76 Safety Critical Elements, grouped into 26 SCE types. Based on the criticality assessment, 4 SCEs were classified as high criticality, 9 as medium criticality, and 13 as low criticality. The most critical SCEs were HC Pipework, Level Indicator, Fixed Point Flammable Gas Detectors, and Flame Detectors. These findings demonstrate that the HAZOP-based approach effectively identifies Major Accident Hazards and establishes priorities for Safety Critical Element management, providing a practical basis for improving process safety and operational reliability in natural gas distribution facilities.